2020
DOI: 10.1111/hae.14075
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fenton reaction is a novel mechanism to explain the therapeutic effect of intra‐articular injection of PRP in patients with chronic haemophilic synovitis

Abstract: Introduction and Aim: Haemarthroses cause major morbidity in haemophilia resulting in chronic haemophilic synovitis (CHS) and arthropathy. Oxidation of haemoglobin-coupled iron released in synovium after haemolysis induces chondrocytes death and cartilage damage, allowing postulate using iron-chelating drugs as potential therapeutic tool for haemophilic joint damage. Considering that albumin, the most abundant plasma protein, is a physiologic iron chelator, we aim to demonstrate that impediment of haemoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Our previous, in vitro, experimental study demonstrated that oxidation of Hb (hemoglobin) to MeHb was completely inhibited either by PRP, PPP or albumin as a physiologic iron chelator and ROS scavenger, it is possible that plasma albumin contributes to the anti-oxidative role of PRP. This could explain the therapeutic effect of intra-articular joint injection of PRP in patients with haemophilia (31). It is also feasible that the albumin applied with the PRP, reduces the amount of intra-articular ROS and prevents the degradation of hyaluronic acid.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous, in vitro, experimental study demonstrated that oxidation of Hb (hemoglobin) to MeHb was completely inhibited either by PRP, PPP or albumin as a physiologic iron chelator and ROS scavenger, it is possible that plasma albumin contributes to the anti-oxidative role of PRP. This could explain the therapeutic effect of intra-articular joint injection of PRP in patients with haemophilia (31). It is also feasible that the albumin applied with the PRP, reduces the amount of intra-articular ROS and prevents the degradation of hyaluronic acid.…”
Section: Discussionmentioning
confidence: 98%
“…Acta Orthopaedica Belgica, Vol. 87 -4 -2021 hypothesis that ROS are responsible for the accelerated degradation of HA in rheumatoid joints (29,31).…”
Section: Discussionmentioning
confidence: 99%
“…PRP interfered with the conversion of haemoglobin to methaemoglobin and was effective in patients with chronic haemophilic synovitis pain and bleeding episodes. 56…”
Section: Mechanism Of Action Of Prp With a Focus On Inflammationmentioning
confidence: 99%
“…5 In addition, and in the context of CHS, we have recently demonstrated that dampening haemoglobin oxidation (and the consequent tissue damage) by plasma is a possible new and non-canonical mechanism underlying the therapeutic effect of PRP in CHS. 6 In this sense, three different clinical groups including ours at the Hospital Fernández in Argentina, have reported that the intraarticular injection of PRP reduces the bleeding episodes in patients with CHS and improves clinical parameters of articular damage. [7][8][9] However, the therapeutic mechanisms underlying PRP in CHS remain to be elucidated, leading to questioning the use of PRP in this pathology.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, plasma offers a fibrin scaffold for regeneration and controls the proliferative and oxidative homeostasis during wound healing 5 . In addition, and in the context of CHS, we have recently demonstrated that dampening haemoglobin oxidation (and the consequent tissue damage) by plasma is a possible new and non‐canonical mechanism underlying the therapeutic effect of PRP in CHS 6 . In this sense, three different clinical groups including ours at the Hospital Fernández in Argentina, have reported that the intraarticular injection of PRP reduces the bleeding episodes in patients with CHS and improves clinical parameters of articular damage 7–9 .…”
Section: Introductionmentioning
confidence: 99%